1998
DOI: 10.4018/jgim.1998070103
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of Arab Culture and Information Technology Transfer

Abstract: Research Methods and Sampling Research Methods and Sampling Research Methods and Sampling Research Methods and Sampling Research Methods and SamplingThe research reported in this paper explores the development of a qualitative research strategy designed to determine the salient cultural and social variables for ITT among Arab-Americans business people and young Arab adults living in the U.S., and a sample of middle class Arabs living in five countries. The ultimate goal of the overall research project is to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
148
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(152 citation statements)
references
References 27 publications
2
148
0
2
Order By: Relevance
“…Loyalty to national traditions is seen as an impediment in focus groups of Arab businessmen [3]. Empirical Perceived near-term usefulness has a more significant influence on intention to use than perceived longterm usefulness in a US sample [29].…”
Section: B Cultural Dimension and Ict Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Loyalty to national traditions is seen as an impediment in focus groups of Arab businessmen [3]. Empirical Perceived near-term usefulness has a more significant influence on intention to use than perceived longterm usefulness in a US sample [29].…”
Section: B Cultural Dimension and Ict Acceptancementioning
confidence: 99%
“…Empirical IT support for individual or cooperative work practices affects acceptance [17]. Empirical Kinship groups and work groups act as references for Arab workers in decisions about IT [3]. Empirical Time orientation…”
Section: B Cultural Dimension and Ict Acceptancementioning
confidence: 99%
“…Also, they indicated that differences in Arabic culture and society have an influence on how new IT is accepted, viewed and utilized among users [48].…”
Section: In Summarymentioning
confidence: 99%
“…Hill et al [48] stated: "As most technology is designed and produced in developed countries, it is culturally-biased in favor of those developed countries' social and cultural systems." Also, they indicated that differences in Arabic culture and society have an influence on how new IT is accepted, viewed and utilized among users [48].…”
Section: In Summarymentioning
confidence: 99%
“…A high masculine culture is highly related to interpersonal presence, so using technologies such as e-mail would not be favoured. In strong feminine cultures, face-to-face communications with rich interactional cues are necessary (Hill et al, 1998).…”
Section: Masculinity-femininitymentioning
confidence: 99%